2023
DOI: 10.1186/s12889-023-15039-6
|View full text |Cite
|
Sign up to set email alerts
|

Psychoactive substance abuse among commercial bus drivers in Umuahia, Abia State, South-Eastern Nigeria: an uncontrolled “epidemic” with attendant road traffic crashes

Abstract: Background information The unprecedented depletion of the productive workforce has been majorly attributed to road traffic crashes (RTCs). The attendant consequences of this depletion have been found to constitute a serious global public health challenge, with the use of psychoactive substances among drivers implicated in every three of five motor vehicle accidents. Hence, this study assessed the pattern and explored the determinants of substance abuse among commercial bus drivers in Umuahia, A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The findings of the current study reflect the vast majority of the drivers had poor knowledge of psychoactive substance hazards as physical, biological, psychosocial, and community hazards. These results are in agreement with the study Akande, Et Al, (2023). The study showed that over half and more than two-thirds of the drivers had overall poor knowledge and poor perception of psychoactive side effects.…”
Section: Regardingsupporting
confidence: 92%
“…The findings of the current study reflect the vast majority of the drivers had poor knowledge of psychoactive substance hazards as physical, biological, psychosocial, and community hazards. These results are in agreement with the study Akande, Et Al, (2023). The study showed that over half and more than two-thirds of the drivers had overall poor knowledge and poor perception of psychoactive side effects.…”
Section: Regardingsupporting
confidence: 92%
“…South-Eastern Nigeria identified alcohol and cigarettes as the most commonly used substances (Akande et al, 2023). Additionally, a study conducted in Kisenyi Slum, Kampala District of Uganda, revealed a high prevalence of drug abuse among youths, with Nigeria having the highest drug prevalence rate (Nakibuuka & Nalubega, 2022).…”
Section: Prevalence Of Drug and Substance Use And Commonly Used Drugs...mentioning
confidence: 99%
“…The independent variables included in the study and identified based on a literature review [19] [20] [21] [22] [23] [29] and empirical analysis of the context were:…”
Section: Variables and Measurementsmentioning
confidence: 99%